2012
DOI: 10.1016/j.neuroscience.2012.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Orexinergic signaling mediates light-induced neuronal activation in the dorsal raphe nucleus

Abstract: Seasonal affective disorder (SAD), a major depressive disorder recurring in the fall and winter, is caused by the reduction of light in the environment, and its depressive symptoms can be alleviated by bright light therapy. Both circadian and monoaminergic systems have been implicated in the etiology of SAD. However, the underlying neural pathways through which light regulates mood are not well understood. The present study utilized a diurnal rodent model, Arvicanthis niloticus, to explore the neural pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 62 publications
7
55
0
Order By: Relevance
“…They expand the scope of retinohypothalamic projections described previously (50)(51)(52)(53). In the context of the present study, it is tempting to propose that modulation of these peptidergic hypothalamic neurons by light, which, at best, is incompletely documented (54)(55)(56), may trigger some of the affective, autonomic, and hypothalamic symptoms. Specifically, altered dopaminergic activity can facilitate anger and irritability (57)(58)(59)(60), fear, panic, anxiety, and stress (61), altered oxytocinergic activity can reduce stress, anxiety, and fear and facilitate the relaxing, calming, soothing, and happy affects (62,63); altered orexinergic, MCHergic, and histaminergic activity can facilitate the perception of sleepiness and hunger (64-66), altered vasopressinergic activity can facilitate thirst (67), and many of these peptidergic neurons can promote yawning (68,69), salivation (70,71), lacrimation, nasal congestion, and rhinorrhea (64).…”
Section: Discussionsupporting
confidence: 70%
“…They expand the scope of retinohypothalamic projections described previously (50)(51)(52)(53). In the context of the present study, it is tempting to propose that modulation of these peptidergic hypothalamic neurons by light, which, at best, is incompletely documented (54)(55)(56), may trigger some of the affective, autonomic, and hypothalamic symptoms. Specifically, altered dopaminergic activity can facilitate anger and irritability (57)(58)(59)(60), fear, panic, anxiety, and stress (61), altered oxytocinergic activity can reduce stress, anxiety, and fear and facilitate the relaxing, calming, soothing, and happy affects (62,63); altered orexinergic, MCHergic, and histaminergic activity can facilitate the perception of sleepiness and hunger (64-66), altered vasopressinergic activity can facilitate thirst (67), and many of these peptidergic neurons can promote yawning (68,69), salivation (70,71), lacrimation, nasal congestion, and rhinorrhea (64).…”
Section: Discussionsupporting
confidence: 70%
“…Light received by the retina stimulates hypothalamic orexinergic neurons in the hypothalamic suprachiasmatic nucleus (SCN) and in the serotonergic nucleus in the dorsal raphe (DRN; Adidharma et al 2012). The SCN is a principal circadian clock and orexin is a neuropeptide regulating the sleep/wake cycle.…”
Section: Discussionmentioning
confidence: 99%
“…ICC was carried out as in previous studies [1, 7] using the primary antibodies TH (1:5000, sc-7847, Santa Cruz) or SST (1:10,000, sc-13099, Santa Cruz). Sections were then processed with the avidin-biotin-immunoperoxidase (ABC) technique using DAB as the chromogen.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we found that hypothalamic neurons containing the neuropeptide orexin are likely to play a role in mediating the effects of light on mood and anxiety. In grass rats, orexin neurons show light-induced activation following acute light exposure [1], and also respond to chronic changes in lighting condition, such that daytime light deficiency leads to a reduction in the number of orexin-expressing neurons [7]. Additionally, treating grass rats housed in summer-like bright light conditions with a selective orexin receptor 1 (OX1R) antagonist induced depression- and anxiety-like behaviors [7].…”
Section: Introductionmentioning
confidence: 99%